The Transformation of the Role of Mosques as Social Economic Institutions: an Empirical Study at the Al Akbar National Mosque in Surabaya - Ubaid Aisyul Hana (MALIA: Jurnal Ekonomi Islam, 2024)
Mosques in the modern era not only serve as places of worship but also have great potential as centres for social and economic empowerment of the community.  The majority of Indonesian mosques have not yet fully utilized this strategic role.  The purpose of this study is to examine how the National Al Akbar Mosque in Surabaya integrates social, economic, and religious empowerment to create a mosque-based business model.  Field observations, in-depth interviews with mosque administrators, business owners, and attendees, as well as written documentation, were used to gather data for this qualitative case study. Through three primary strategies—the relocation and organization of street vendors (PKL), the creation of a Mosque-Owned Business Entity (BUMM), and the execution of community economic empowerment initiatives based on Islamic spirituality—the National Mosque Al Akbar Surabaya has effectively developed an innovative mosque-based economic model, according to the research findings.  By creating jobs, providing access to sharia-compliant financing, and allocating productive zakat, this strategy has had a real impact on enhancing the welfare of worshippers and the local community.  The study's conclusions suggest that, with proper management and adherence to Islamic principles, mosques can serve as hubs for socioeconomic change. In order to guarantee the sustainability of mosque-based economic models in Indonesia, this study suggests bolstering mosque economic institutions, digitizing banking systems, and encouraging cross-sectoral synergies.